Peran Lembaga Internasional dalam Menegakkan Hukum Humaniter: Studi Atas Upaya PBB dan Palang Merah Internasional dalam Konflik Bersenjata - Sudrajat, Mochamad Andri Wahyu; Johor, Wan Saiful Bahari Bin Wan; Susilo, Tarsisius; Yadi, Rahman; Prasetyo, Joko (Universitas Pahlawan Tuanku Tambusai, 2025)
Armed conflicts that continue to occur in various parts of the world have caused immense suffering to civilian populations, thereby demanding the enforcement of International Humanitarian Law (IHL) as a legal framework to protect victims of war. In this context, the role of international institutions becomes crucial, particularly the United Nations (UN) and the International Committee of the Red Cross (ICRC), which possess distinct yet complementary mandates and mechanisms. This study aims to thoroughly analyze the contributions and challenges faced by both institutions in upholding international humanitarian law. The research employs a library research method with a qualitative-descriptive approach, based on official documents, academic journals, reports from international organizations, and theoretical analyses related to humanitarian law. The findings reveal that the UN plays a normative, political, and security role through peacekeeping missions, Security Council resolutions, and support for international tribunals. Meanwhile, the ICRC contributes operationally by providing direct humanitarian assistance, maintaining neutral advocacy, and promoting humanitarian law education. The collaboration between both institutions proves essential in ensuring civilian protection, although it is not without challenges such as politicization, field access constraints, and conflicts of interest among international actors. Effective institutional synergy, reformed coordination mechanisms, and adaptation to the evolving nature of contemporary conflicts are critical for enhancing the future effectiveness of humanitarian law enforcement.